A Comprehensive Pharmacological Review of Natural Products Active Ingredients in Ulcerative Colitis - Hong, Ran; Zhang, Zengni; Sun, Xiaoli; Chen, Yajuan; Wei, HuiLin; Chen, Qiulin; Zhou, Lisha; Zhou, Xia; Chen, Wenwen; Wan, Jun (Natural Products Journal, The, 2026)
Ulcerative colitis (UC) is a nonspecific, prolonged, and recurrent autoimmune disease characterized by diarrhea, mucopurulent stools, and abdominal pain. Modern medicine believes that the disease is related to infectious, genetic, psychiatric, allergic and especially autoimmune factors, but the exact cause is unknown. Given that the disease is recurrent, aggravating and persistent, and has a certain cancer rate, it is increasingly urgent to find effective treatments. It has been proved that UC is related to the abnormal regulation of signaling pathways in the body, dysregulation of intestinal ecology, and intestinal immune disorders, and natural products active ingredients for the treatment of UC have the advantage of long-term efficacy and less toxic side effects compared to existing drugs. This paper reviews the pharmacological mechanisms associated with UC to gain insight into the therapeutic mechanisms of natural products active ingredients for UC and to better understand the advantages and potential of natural products active ingredients in the treatment of UC. This will provide guidance for the development of new therapeutic strategies and drugs, and offer new hope for improving the quality of life of patients with UC.
Keywords: intestinal microenvironment